Current control in the grid connection of the double-output induction generator linked to a variable speed wind turbine - Carlos J. Ramos (2002)
The output power of present wind turbines is continuously increasing. At high power levels, to limit mechanical stresses and power surges in the grid it is necessary to use speed control systems. The double-output induction generator (DOIG) system is an excellent solution to adjust the speed over a wide range. At present the two converters associated with the DOIG use high power IGBTs with medium switching frequencies in order to optimise the current waveform in the generator and in the grid. The two converters need a high performance control system operating with high sampling frequencies and complex control algorithms. The voltage source IGBT converter connected to the grid controls the active and reactive power supplied and imposes a low level of harmonic distortion. In this paper it is presented the results obtained with such a system.